Peran Fiqh Tasamuh dan Aqaliyyah dalam Menguatkan Ukhuwah di Tengah Isu SARA perspektif fiqih kontemporer - A Muhammad Batara; Muhammad Shuhufi; Misbahuddin M (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
The rise of SARA (Ethnicity, Religion, Race, and Intergroup Relations) issues in Indonesia poses a serious challenge to the unity of a multicultural society. This study aims to analyze the role of fiqh tasamuh (tolerance) and fiqh aqaliyyah (rationality) in strengthening ukhuwah through the perspective of contemporary fiqh. The research method employed is library research by examining classical and modern literature. The findings indicate that fiqh tasamuh serves as an instrument of tolerance in mitigating conflicts, while fiqh aqaliyyah emphasizes rational and maslahat-oriented approaches in addressing SARA-related issues. The integration of both within contemporary fiqh produces a contextual, solution-oriented, and applicable paradigm of Islamic law. In conclusion, strengthening ukhuwah through tasamuh and aqaliyyah has implications for creating an inclusive and harmonious society, with recommendations for enhancing contemporary fiqh literacy in education and public policy.